Exploring the influence of wheelchair-user interface and personal characteristics on ischial tuberosity peak pressure index and gradient in elite wheelchair basketball players - Peters, J.; Rice, I.; Bull, T. (Adapted Physical Activity Quarterly, 2023)
This pilot study investigated the relationship between personal and wheelchair factors on skin pressures at the ischial tuberosity in wheelchair basketball players. Seventeen wheelchair basketball players (7 male and 10 female) were evaluated during static and dynamic propulsive conditions while peak pressure index and peak pressure gradient were recorded with an interface pressure mat. The results showed that greater seat dump angles and backrest heights were negatively associated with the peak pressure index. Therapeutic cushion use was moderately associated with a reduced peak pressure gradient. Higher-class players used chair configurations associated with augmented pressure; however, classification status alone was not associated with pressure magnitude. Body mass index was negatively correlated with the static peak pressure gradient at levels approaching significance (p < .10). In conclusion, greater seat dump angles and backrest heights may provide pressure relief, whereas greater body mass index and therapeutic cushion use may reduce pressure gradients.